2000
DOI: 10.1159/000013618
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Estimate of the Effect of the Serum Albumin Level on the Anion Gap

Abstract: Background: The serum anion gap (serum [Na+]-Cl-]-[CO2]) is still the first-line approach to metabolic acidosis. However, while it is generally acknowledged that hypoalbuminemia mandates a downward adjustment of the expected anion gap, a specific correction factor for the anion gap in the face of low serum albumin has never been demonstrated. Methods: We reviewed initial laboratory data from 432 consecutive patients admitted or transferred to the medical intensive care unit at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 5 publications
0
14
0
2
Order By: Relevance
“…Surprisingly, it is only within the last 13 years that a correction factor has been developed that can be introduced into clinical practice. These studies revealed that the anion gap is reduced by 2.3-2.5 mEq/L per gram of fall in serum albumin concentration, whereas it is increased to a similar degree with a rise in serum albumin concentration (21,22).…”
Section: Definition and Characterization Of The Normal Serum Anion Gapmentioning
confidence: 97%
“…Surprisingly, it is only within the last 13 years that a correction factor has been developed that can be introduced into clinical practice. These studies revealed that the anion gap is reduced by 2.3-2.5 mEq/L per gram of fall in serum albumin concentration, whereas it is increased to a similar degree with a rise in serum albumin concentration (21,22).…”
Section: Definition and Characterization Of The Normal Serum Anion Gapmentioning
confidence: 97%
“…For every increase of 1 g per deciliter in the plasma albumin level, one should subtract 2.5 mmol per liter from the calculated value of the plasma anion gap. 4,5 Even with this adjustment, it appears that the net negative valence on albumin is increased when there is an appreciable decrease in the effective arterial blood volume, and hence there is a higher value for the plasma anion gap. 6 The relation between the increase (Δ) in the plasma anion gap and the decrease (Δ) in the plasma bicarbonate concentration -which is commonly referred to as delta-delta (Δ-Δ) -is used to provide an estimate of the magnitude of the acid load and to detect the presence of coexisting metabolic acid-base disorders.…”
Section: Pl a Sm A Bic A R Bonate A Nd The Pl A Sm A A Nion Ga Pmentioning
confidence: 99%
“…Kritik hasta grubunda hipoalbüminemi ile azalmış anyon gap birlikteliği literatürde önemli bir yer tutmaktadır (6)(7)(8). Fedman ve arkadaşları 1ay-102 yaş aralığında albumin çalışılan 5328 hastayı incelemiş ve hiperalbuminemi saptanan hastalarda hiperalbumineminin artmış anyon gap ile birlikteliğine dikkat çekmiştir (2).…”
Section: Discussionunclassified